Transcriptional Landscape of a blaKPC-2 Plasmid and Response to Imipenem Exposure in Escherichia coli TOP10 - Jousset, Agnès B.; Rosinski-Chupin, Isabelle; Takissian, Julie; Glaser, Philippe; Bonnin, Rémy A.; Naas, Thierry (Frontiers in Microbiology, 2018)
The diffusion of KPC-2 carbapenemase is closely related to the spread of Klebsiella pneumoniae of the clonal-group 258 and linked to IncFIIk plasmids. Little is known about the biology of multi-drug resistant plasmids and the reasons of their successful dissemination. Using E. coli TOP10 strain harbouring a multi-replicon IncFIIk-IncFI blaKPC-2-gene carrying plasmid pBIC1a from K. pneumoniae ST-258 clinical isolate BIC-1, we aimed to identify basal gene expression and the effects of imipenem exposure using whole transcriptome approach by RNA sequencing (RNA-Seq). Independently of the antibiotic pressure, most of the plasmid-backbone genes were expressed at low levels. The most expressed pBIC1a genes were involved in antibiotic resistance (blaKPC-2, blaTEM and aph(3’)-I), in plasmid replication and conjugation, or associated to mobile elements. After antibiotic exposure, 34% of E. coli (pBIC1a) genome was differentially expressed. Induction of oxidative stress response was evidenced, with numerous upregulated genes of the SoxRS/OxyR oxydative stress regulons, the Fur regulon (for iron uptake machinery), and IscR regulon (for iron sulfur cluster synthesis). Nine genes carried by pBIC1a were up-regulated, including the murein DD-endopeptidase mepM and the copper resistance operon. Despite the presence of a carbapenemase, we observed a major impact on E. coli (pBIC1a) whole transcriptome after imipenem exposure, but no effect on the level of transcription of antimicrobial resistance genes. We describe adaptive responses of E. coli to imipenem-induced stress, and identified plasmid-encoded genes that could be involved in resistance to stressful environments.